2015
DOI: 10.13045/acupunct.2015008
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Amount of Stimulus Differences According to Pharmacopuncture Injected dose and Characters Method

Abstract: Objectives : This study was designed to discover the difference in stimulation effect when the volume and insertion method of mountain ginseng pharmacopuncture was varied. Methods : 48 healthy people were randomly injected with 0.1, 0.3, 0.5, and 0.7 cc of mountain ginseng pharmacopuncture, perpendicularly or transversely at acupoints LI 9 and LI 10 . The subjects noted their level of stimulation on a 100 mm visual analog scale(VAS) immediately after, 3 minutes after, and 5 minutes after the treatment. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Wild ginseng pharmacopuncture injected at acupoints (ST36 and ST37) did not significantly change the acupuncture sensations as compared with other types of complex-herb pharmacopuncture (e.g., BUM pharmacopuncture made of Calculus Bovis, Fel Ursi, Moschus) and saline injection [20]. Another study showed that only the volume of injected solution, but not the stimulation methods (perpendicular versus transverse injection) at acupoints, affected the subjective intensity reporting of pharmacopuncture stimulation [21].…”
Section: Physiological Response To Ginseng Pharmacopuncture In Human mentioning
confidence: 92%
See 2 more Smart Citations
“…Wild ginseng pharmacopuncture injected at acupoints (ST36 and ST37) did not significantly change the acupuncture sensations as compared with other types of complex-herb pharmacopuncture (e.g., BUM pharmacopuncture made of Calculus Bovis, Fel Ursi, Moschus) and saline injection [20]. Another study showed that only the volume of injected solution, but not the stimulation methods (perpendicular versus transverse injection) at acupoints, affected the subjective intensity reporting of pharmacopuncture stimulation [21].…”
Section: Physiological Response To Ginseng Pharmacopuncture In Human mentioning
confidence: 92%
“…Among the case reports, 18 used wild ginseng pharmacopuncture in patients with cancer [lung cancer (n = 17, patients); hepatocellular carcinoma, prostate cancer, colorectal cancer, or pancreatic cancer (n = 2, respectively); cervical cancer, thymus cancer, breast cancer, Signet ring cell carcinoma, bronchioloalveolar carcinoma, or tubulovillous adenoma (n = 1, respectively)] [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. One hundred patients with rhinitis [56], 23 with skin wrinkles [21], three with amyotrophic lateral sclerosis (ALS) [53], and one with Behçet's disease, hepatitis, hepatocirrhosis [52], cervical dysplasia [54], neurofibroma [14], and acute demyelinating encephalomyelitis [55] were included in the systematic review. A RCT included 102 patients with depression and compared the effect and AEs of combined therapy composed of ginseng polysaccharides pharmacopuncture, Bupleurum pharmacopuncture, and paroxetine with those of paroxetine-only treatment [16].…”
Section: Participants and Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both PA and CSI are injected into the affected lesion to exert anti-inflammatory effects [ 15 , 20 ]. PA and HD also have volume effects, with the injected material distending the surrounding tissue [ 3 , 21 ]. However, CSI and HD are injected into intra-articular lesions, presenting an infection risk, and possibly negatively impacting the surrounding rotator cuff tissue [ 3 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacopuncture is a combination of acupuncture and medication, and is a new therapy in which a purified herbal medicine is injected at an acupoint. It is widely used in China and Korea, and is also known as acupoint injection, herbal acupuncture, aqua acupuncture, and aquapuncture [16]. With its increasing use, various studies on pharmacopuncture have been initiated and are ongoing.…”
Section: Introductionmentioning
confidence: 99%